Anti-Microbial Activity of Chloramphenicol from Streptomyces sp.10CM9. (3rd July 2015) - Ozcan, Kadriye; Uzel, Ataç; Bedir, Erdal
Abstract: An antimicrobial agent, chloramphenicol, was isolated from Actinobacteria 10CM9. The strain was isolated from lake sediment collected from Erçek Lake, Van (38°29'57.76"N and 43°33'10.98"E) and AIA medium was used as a isolation medium. 16S rRNA gene sequence analysis that showed the strain belongs to the genus Streptomycetes. A fermentation study in AIA broth medium (3L) followed by extraction with EtOAc afforded 105 mg of crude extract. A bioactivity-guided fractionation by Open Column chromatography on silica gel led to the isolation of one secondary metabolite (10CM19-01, 31 mg). Structures of the metabolites were established as chloramphenicol, by means of NMR ( 1 H, 13 C and COSY) data. Antimicrobial activity of 10CM9 was tested by microdilution method against enteropathogenic Escherichia coli 0157:H7 (RSKK 234), methicillin resistant Staphylococcus aureus ATCC 43300, vancomycin resistant Enterococcus faecium DSMZ 13590, Candida albicans DSMZ 5817 and Pseudomonas aeruginosa ATCC 27853. As a result, 0.5 μg/ml, 0.5 μg/ml and 1 μg/ml MIC values were observed against Escherichia coli 0157:H7, Enterococcus faecium and Staphylococcus aureus, respectively.